Relações entre provimento de cargos e estilos de liderança nas práticas de gestão escolar: uma pesquisa bibliográfica - Gava, Shirley Aparecida (2022)
This investigation was carried out within the scope of the Study and Research Group on School Organization: Democracy, Human Rights and School Administrators’ Development – DEFORGES. The theme in which it is inserted is the democratic management of public schools, having as object the different ways of filling the positions of school principals, in the different school systems existing in Brazil, and the relationships between these ways and principals’ leadership styles. The investigation was carried out in order to problematize the following question: what are the relationships between forms of provision of principals’ positions/functions and school leadership styles? Thus, the general objective was to identify the forms of provision for the position/function of school principals and their leadership styles. The specific objective was to clarify these relationships, with regard to school administration practices, referenced in national digital publications, derived from empirical research, in the digital databases SciELO - Brazil, Google Scholar, Portal de Periódicos da CAPES and Biblioteca Digital Brasileira de Teses e Dissertações, between the years 2011 and 2021. Methodologically, it is a qualitative and exploratory investigation in education, having the bibliographic research as method and the content analysis as technique. The instrument used to process and organize the data was the MAXQDA22 software. Among the results obtained, the predominance of the managerial style of leadership stands out, regardless of the forms of provision of principal manship positions/functions raised in this research, so the practices of these professionals have prioritized bureaucratic and administrative aspects of everyday school life. In this way, school principals, as expected institutional leaders, by disregarding other leaders, as well as by neglecting the importance of collegiate and social participation in decision-making, have contributed to the maintenance of impermeable organizational structures, not only hindering and/or preventing school democracy from manifesting itself, but also maintaining the hierarchy overload on the relationships among diverse school agents, thus reinforcing individualized forms of power and authoritarian actions in public schools.